2013
DOI: 10.1016/j.tet.2012.12.007
|View full text |Cite
|
Sign up to set email alerts
|

1,2,4-Oxadiazoles from cycloreversions of oxadiazabicyclo[3.2.0]heptenes: 1-azetines as thiocyanate equivalents

Abstract: Leave this area blank for abstract info.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…2-Methylthio-4-(naphth-2-yl)-1-azetine 5 (Scheme 1) has been synthesized by us before [9,10] and used in cycloaddition reactions. Previously, the 1-azetine was obtained by alkylation of the readily available [9,10] thiolactam 7, as shown in Scheme 1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2-Methylthio-4-(naphth-2-yl)-1-azetine 5 (Scheme 1) has been synthesized by us before [9,10] and used in cycloaddition reactions. Previously, the 1-azetine was obtained by alkylation of the readily available [9,10] thiolactam 7, as shown in Scheme 1.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the 1-azetine was obtained by alkylation of the readily available [9,10] thiolactam 7, as shown in Scheme 1. When this reaction mixture is worked up and purified immediately, the 1-azetine is the major product, as already reported [9,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No reactions of the imine present in the thiazete 1,1-dioxide (5a) were observed, and the starting material was returned unchanged in all cases, a huge disappointment given that we had shown that the imine within the 1-azetine system reacts easily with both nitrile oxides and cyclopropenones. [21][22][23][24] Other 1,3-dipoles (nitrile ylides, nitrilimines, nitrones, aryl azides and azomethine ylides) and dienes were found to be similarly unreactive. Interestingly, when the cyclopropenone reaction was attempted in the presence of a Lewis acid, a reaction was observed.…”
Section: Synthesis and Reactivity Of Isothiazole 11-dioxides And Thimentioning
confidence: 99%
“…25 Nonetheless, we have shown that 1-azetines are able to act as precursors for the synthesis of benzoisoquinolines, 21 homotropane related heterocycles 22 and pyridines 23 via a formal [3+2]-cycloaddition reaction with cyclopropenones (which act as all-carbon 1,3-dipole equivalents) as well as acting as dipolarophiles for the synthesis of 1,2,4-oxadiazoles 24 via reaction with nitrile oxides. As a result of these successes, and given our interest in the β-sultam nucleus, we wished to explore the chemistry of the unsaturated β-sultam system, the thiazete 1,1-dioxide (4).…”
Section: Figure 1 Heterocycles Of Interest In This Workmentioning
confidence: 99%